A Public Health Learning Collaborative on Climate Change for Urban Health Departments, 2016-2018 - Rudolph, Linda (Public Health Rep, 2020)
OBJECTIVES: The objective of this project was to demonstrate and assess approaches of urban local health departments (LHDs) to simultaneously address climate change, health, and equity; incorporate climate change into program practice; and participate in their jurisdiction’s climate change work. METHODS: From January 2016 through March 2018, the Center for Climate Change and Health created learning activities, networking and relationship-building opportunities, communication platforms, and information sharing for 12 urban LHDs in the United States. We used administrative data and conducted interviews with participants and key informants to assess success in meeting learning collaborative goals. RESULTS: LHDs developed diverse projects that incorporated internal capacity building, climate and health vulnerability assessments, surveillance, and community engagement. Projects fostered greater LHD engagement on climate change, broadened community partnerships, and furthered LHD integration into jurisdictions’ climate planning. LHD engagement helped shift the dialogue in the community and jurisdiction about climate change to include public health. CONCLUSIONS: LHDs have skills and expertise to rapidly partner with other governmental agencies and community-based organizations and to help communities identify vulnerabilities, take action to reduce the health harms of climate change, and—through Health in All Policies approaches and community partnerships—to ensure that climate policies are optimized for positive health and equity outcomes.